CORPUS ANALYSIS OF HIGH SCHOOL LEARNERS’ RESEARCH PAPERS IN HEALTH SCIENCE (2016-2019) - Pastare, Anita; Krumina, Aira Aija; Karulis, Miervaldis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In Latvia, the learners of secondary school as a requirement gets acquainted with basics of research – selection of literature, data collection and processing, communication and presentation skills.The present article deals with an analysis of the themes and texts (corpus) of the research papers (RP) in Health Science worked out by the authors of the top-ranked RP presented in the Scientific Conference of High School Learners of Latvia from 2016 to 2019. A logical inductive content analysis of features specific to each RP, and sequential categorization and grouping into a higher level of components were performed. The quantitative data were processed by using AntConc, IBM SPSS Statistics 22 and Microsoft Excel software.The aim of the research was to find out the themes and content variations of RP, and the characteristics of the language – tokens, types and keywords.The results show that there is a thematic uniformity in RP. The statistical characteristics of language differ in terms of lexical diversity and the frequency of keywords and their collocations. Mostly individual keywords dominate.The results obtained can be used to develop recommendations for learners and teachers as a model for theme selection, presentation of research and criteria for evaluating RP.